TRANSFORMATION OF UKRAINIAN NATIONAL IDEA: THE INFLUENCE OF RELIGION AND CHURCH - Ломака, І. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The article analyzes the role of religion and church in the context of Ukrainian national consciousness and national idea in terms polikonfesiynosti Ukrainian society. Through analysis of the functioning of religious – spiritual factor in the Ukrainian society concluded that further development of the Ukrainian nation requires not only the ethnic, political or cultural, but also religious – church consolidation. The basis of national consciousness, taking into account the peculiarities of Ukraine should be universally recognized democratic values, because throughout the history of Ukrainian state there was an evolution and transformation of the Ukrainian national idea, which certainly was an element of religion.